Raising my rainbow : adventures in raising a fabulous, gender creative son - Duron, Lori (Broadway Books, 2013)
Whereas her older son, Chase, is a Lego-loving, sports-playing boy's boy, Lori's younger son, C.J., would much rather twirl around in a pink sparkly tutu, with a Disney Princess in each hand while singing Lady Gaga's "Paparazzi." C.J. is gender variant or gender nonconforming, whichever you prefer. Whatever the term, Lori has a boy who likes girl stuff<U+2014>really likes girl stuff. He floats on the gender-variation spectrum from super-macho-masculine on the left all the way to super-girly-feminine on the right. He's not all pink and not all blue. He's a muddled mess or a rainbow creation. Lori and her family choose to see the rainbow. Written in Lori's uniquely witty and warm voice and launched by her incredibly popular blog of the same name, Raising My Rainbow is the unforgettable story of her wonderful family as they navigate the often challenging but never dull privilege of raising a slightly effeminate, possibly gay, totally fabulous son.